Fenomena K-Pop di Indonesia Serta Implikasinya Terhadap Penguatan Rasa Cinta Tanah Air Gen-Z - Wiwoho, Husnun Nabila Putri; Mari’a, Dina Haniam; Hanifah, Najwa (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Gen Z is a demographic group born between the mid-1990s and early 2010s, who grew up in the midst of the information and technology era. The history of K-pop as part of the Korean Wave or Hallyu has reached global popularity since the early 2000s, influencing popular culture in various parts of the world, including Indonesia. This article aims to understand how exposure to K-pop culture affects the strengthening of Gen Z's sense of patriotism in Indonesia. By examining the definition of Gen Z, the history of K-pop, and the implications of K-pop on strengthening patriotism. This research uses the literature study method as the main approach. Data was collected through literature review from various sources, including journal articles, books, research reports, and mass media relevant to the topic of K-pop and patriotism. The data analysis technique used was content analysis, which allows researchers to identify and evaluate themes and patterns that emerge from the literature reviewed. The results showed that exposure to K-pop culture can have a negative impact as well as a positive impact on strengthening Gen Z's sense of patriotism in Indonesia. Exposure to foreign cultures such as the K-pop phenomenon certainly allows the loss of national identity, local culture and values to a sense of patriotism or nationalism that should be owned by each individual, but the K-pop phenomenon can also have a positive impact in creating a sense or desire to develop local culture. The implications of K-pop are not only limited to the entertainment aspect, but also affect Gen Z's attitude and perception towards their country and nation.